The importance of internal auditing by independent auditors to a Hi- Tech manufacturing organization: evidence from Walton Hi-Tech Industries PLC - Ahmed, Mahjabin (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.